Analysis of Bone Nonunion in a Child with Lower Fibula Fracture - Yang, Xiang; Zhou, Jianhong (Journal of Contemporary Medical Practice, 2024)
This paper reported a case of a child with old fracture of the lower fibula. After complete examination, the patient underwent "open reduction and elastic intramedullary nail internal fixation + allograft bone grafting of the lower fibula". Reexamination 5 months after operation revealed allograft bone resorption, bone defect and bone nonunion at the fracture end. After that, a second operation was performed in the external hospital, with the method of "bone nonunion incision elastic intramedullary nail extraction after the fracture of the left fibula + plate screw internal fixation + autologous bone grafting". The review four months after the operation showed that autologous bone absorption at the broken end of the fracture resulted in obvious bone defect, loosening of internal fixation, and bone non-union again, and internal fixation was finally removed, and the family gave up further treatment.